Being deified : poetry and fantasy on the path to God - Mosley, David Russell (Minneapolis. : Fortress Press., 2016)
Being deified examines the importance of deification to Christian theology and the place of human creativity in deification. This volume utilizes the work of fantasy writers and poets in order to show the importance of these genres for theology in general and for their importance in human deification.
Stanza 1. Poet and poem: God, creation, and humanity. 1. Before "In the beginning," or "In the beginning God"; the God who is poet and theo-poet -- 2. The poem days 1-5: the stage for deification -- 3. The poem day 6: humanity, the deified -- Stanza II. Pride, evil, and distorted vision. 4. The pride of the poem: auto-deification, distorted sight, and privative evil -- 5. Distorted eyesight and a corrupted cosmos -- Stanza III. The poet enters the poem: incarnation, deification, and a restoration of vision. -- Stanza IV. Participating in the poem: sacraments, liturgy, and human creativity. 7. Participating in the poem: sacramental ontology -- 8. Participating in the poem and theo-poem: human creativity and examples from poetry and fantasy.
Includes bibliographical resources (pages 217-228) and index.
Keywords: Deification (Christianity); Deification (Christianity)